Phytochemical Constituents of F. Sagittifolia Warburg ex Mildbraed & Burret Leaves with Antimicrobial Activity - Olayombo Margaret Taiwo; Olaoluwa Omosalewa Olaoluwa; Olapeju Oluyemisi Aiyelaagbe; Josphat Clement Matasyoh (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2022)
The leaves and bark of Ficus sagittifolia have been used as a cure for stomach and pulmonary disorders, respectively. The bark is edible and is taken against colic. From the leaves of F. sagittifolia, a steroidal glycoside named Stigmast-5,22-diene-3-O-?-D-glucopyranoside 1 and three isoflavonoids named 5-hydroxy-3-(4-hydroxyphenyl)-7-methoxy-4H-chromen-4-one 2, 5-hydroxy-3(4-hydroxylphenyl)-8,8-dimethylpyrano[2,3-f]-chromen-4(8H)-one 3 and 5-hydroxy-3-(4-hydroxyphemyl)-8,8-dimethylpyrano[3,2-g-chromen-4(8H)-one 4 were isolated, and this is the first report of the isolation of these compounds from this plant. The structural elucidation of the compounds was based on 1D and 2D NMR, IR and MS data analyses. Compounds 1 and 2 inhibited the growth of Pseudomonas aeruginosa and Aspergillus Niger at 0.0625 mg/mL, respectively while compounds 2 and 4 were active against Helicobacter pylori at 0.0625 mg/mL. These findings corroborate the ethno-medicinal use of F. sagittifolia leaves as a treatment for stomach disorders.